PEDAGOGICAL AND PSYCHOLOGICAL ASPECTS OF STUDENTS' INTELLECTUAL COMPETENCE DEVELOPMENT - Razikova Lola Tuychievna (Journals Park Publishing, 2023)
One of the important directions of youth policy in Uzbekistan is wide involvement of talented young people in science. Year by year, more favorable conditions and opportunities are created for the comprehensive development of young people. In this article, the content and essence of intellectual ability of students, ways of its development and the problem of development of intellectual abilities of future specialists are interpreted.
Keywords: student, intellect, ability, potential, talent, development, intellectual ability, intellectual competence.